Sixth International Science & Practice Conference “The Theory and Practice of Forensic Science under Current Conditions” - E. R. Rossinskaya (Теория и практика судебной экспертизы)
The article outlines the program of the VI International Science & Practice Conference “The Theory and Practice of Forensic Science under Current Conditions”, dedicated to the memory of Distinguished Lawyer of the Russian Federation Professor Yurii Kuz'mich Orlov. The conference was held January 19–20, 2017 at Kutafin University in Moscow.